Disparities by Gender and Race/Ethnicity in Child Maltreatment and Memory Performance - Brown, Monique J.; Jiang, Yanping; Hung, Peiyin; Haider, Mohammad Rifat; Crouch, Elizabeth (Journal of interpersonal violence, 2022)
Adverse childhood experiences, which include child maltreatment, are a major public health issue nationally. Child maltreatment has been linked to poorer cognitive functioning, which can start in childhood and persist into adulthood. However, studies examining the potential disparities by gender and race/ethnicity are lacking. The aim of this study was to assess the gender and racial/ethnic disparities in the association between child maltreatment and memory performance. Data were obtained from Waves III and IV of the National Longitudinal Study of Adolescent to Adult Health (N = 11,624). Weighted multiple linear regression models were used to assess the associations between sexual abuse, physical abuse, neglect, and child maltreatment score and memory. Models were stratified by gender, race, and ethnicity. Men who were exposed to sexual abuse, neglect and two or three child maltreatment types scored one to three points lower (β = –1.44; 95% CI: –2.83, –0.06; β = –2.41; 95% CI: –3.75, –1.08; β = –3.35; 95% CI: –5.33, –1.37; β = –2.31; 95% CI: –3.75, –0.86) in memory performance compared to men who did not report sexual abuse, neglect, or child maltreatment, respectively. Black respondents who were exposed to sexual abuse scored two points lower (β = –1.62; 95% CI: –2.80, –0.44) in memory performance compared to Black respondents who did not report sexual abuse. Among Other race and Hispanic respondents, those who reported neglect scored four points lower (β = –4.06; 95% CI: –6.47, –1.66; β = –4.15; 95% CI: –5.99, –2.30) in memory performance, respectively, compared to their counterparts who did not report neglect. Gender- and racial/ethnic-responsive memory performance interventions addressing child maltreatment may be beneficial for affected populations.